Is aging a barrier to reprogramming? Lessons from induced pluripotent stem cells - Phanthong, Phetcharat; Raveh-Amit, Hadas; Li, Tong; Kitiyanant, Yindee; Dinnyes, Andras (Biogerontology (Dordrecht), 2013)
The discovery of induced pluripotent stem cells (iPSCs) has the potential to revolutionize the field of regenerative medicine. In the past few years, iPSCs have been the subject of intensive research towards their application in disease modeling and drug screening. In the future, these cells may be applied in cell therapy to replace or regenerate tissues by autologous transplantation. However, two major hurdles need to be resolved in order to reach the later goal: the low reprogramming efficiency and the safety risks, such as the integration of foreign DNA into the genome of the cells and the tumor formation potential arising from transplantation of residual undifferentiated cells. Recently, aging emerged as one of the barriers that accounts, at least in part, for the low reprogramming efficiency of bona fide iPSCs. Here, we review the molecular pathways linking aging and reprogramming along with the unanswered questions in the field. We discuss whether reprogramming rejuvenates the molecular and cellular features associated with age, and present the recent advances with iPSC-based models, contributing to our understanding of physiological and premature aging.